Test of English as Foreign Language (TOEFL) Training for Medical Record Students in Bengkulu - Marita, Yosi; Utami, Elva; Masitah, Siti (DIKDIMAS : Jurnal Pengabdian Kepada Masyarakat, 2022)
In the current era of globalization which is full of challenges and competition, not only high level of education, but everyone is required to have special skills. One of the skill that medical record students must possess is English. This of course makes many students find it difficult to meet the standard of TOEFL score because lack of understanding in English by some students. Through TOEFL training, participants will get listening, writing, and reading tests. The method used in this community service is a descriptive method through a qualitative approach. This method was chosen because it presents data systematically and accurately regarding the facts in the field. Based on the data, it shows that more than 50%, namely 87.5% (21 students) have a TOEFL score above the criteria, which is 425 indicating that there is an increase in the TOEFL score after the training.